REFLEKSI KEMERDEKAAN: BAHASA ISYARAT DI LAYAR KACA - Fajar Kurniawan (Universitas Bina Sarana Informatika, 2017)
When language is spoken through words, speech and gestures (signs) are also combined. However, while language is conveyed in writing through sentences comprising of words and punctuation marks, sign language on the contrary does not use words or punctuation marks but instead uses gestures in the form of signs that are commonly understood by the signer and the recipient. Therefore, sign language is also called nonverbal communication which is a language that does not use words at all and is a part of communication. What we have viewed on television on August 17, 2017 shows that the existence of sign language has become a gift for the 72nd independence day of our nation this year. In other words, it is the freedom that can be enjoyed by people with hearing disability, which is the freedom to gain the same information as other citizens. The presence of sign language used by broadcasting agencies in news programs fulfills language as a means of communication. Not only language as a universal form, but also language as a system as well as a culture. In the context of this paper, it is Deaf Culture.Keywords: Sign Language, Television, Deaf Culture, Communication, Nonverbal Communication.